Inhibition of Mild Steel Corrosion in 1 M HCl Solution by 1-Propanaminium N,N,N-tributyl bromide - Prathibha, B.S.; Kotteeswaran, P.; Bheema Raju, V. (Asian Journal of Chemistry, 2012)
The effect of 1-propanaminium N,N,N-tributyl bromide (TPAB) on the corrosion of mild steel in 1 M HCl solution has been investigated in relation to the concentration of the inhibitor as well as temperature by corrosion monitoring techniques such as polarization measurements and electrochemical impedance spectroscopy. Results obtained revealed that TPAB is a mixed type inhibitor. The adsorption of inhibitor on mild steel surface obeys the Langmuir adsorption isotherm equation. Both thermodynamic and kinetic parameters have been obtained by adsorption theory and kinetic equations. The results obtained by polarization and EIS are in good agreement.